Estimating the Market Effect of a Food Scare: The Case of Genetically Modified StarLink Corn - Carter, Colin A; Smith, Aaron (The Review of Economics and Statistics, 2007)
In 2000, a genetically modified corn variety called StarLink that was not approved for human consumption was discovered in the food-corn supply. To estimate the price impact of this event on the U.S. corn market, we develop the relative price of a substitute method. This method applies not only to the StarLink event but also to rare events in other markets. We find that the contamination led to a 6.8% discount in corn prices and that the suppression of prices lasted for at least a year.